PERENCANAAN TATA KERJA DAN KOORDINASI DALAM MENINGKATKAN KINERJA PEGAWAI DINAS BINA MARGA KOTA BANJARMASIN - Jaya Bahwiyanti (KINDAI, 2017)
Abstract: This study aimed to determine planning and coordination procedures to improve employee performance Highways Agency Banjarmasin, and solutions to overcome obstacles related to planning and coordination of work in improvingemployee performance Highways Agency Banjarmasin. The method used in thisstudy is the evaluation. The population in this study is the Departemen ofhighways employee Banjarmasin many as 73 people analyzed qualitatively. Theresults showed 1) planning and coordination at the working procedures of theDepartement of Highways Banjarmasin in improving employee performanceincludes activities intoor out of, looks not show maximum results, 2) constraintplanning and coordination of work by the Highways Agency in Banjarmasinimproving the effectiveness of such: a)Lack of human resources quantity asemployees tasked with administration and operational techniques to handle thedevelopment of physical development in the city of Banjarmasin, b) lack ofeducation and training obtained by an employee who handles tackle the economic problems in the development physical area. While the office is related to external factors such as: a)Lack of informant and data to the importance of the development of physical development in the city of Banjarmasin and, b) lackof cooperation between departments / againces that are competent.Keywords: Planning, Coordination and PerformanceAbstrak: Penelitian ini bertujuan untuk mengetahui perencanaan tata kerja dankoordinasi dalam meningkatkan kinerja pegawai Dinas Bina Marga KotaBanjarmasin, dan solusi yang menyangkutperencanaan tata kerja dan koordinasi dalam meningkatkan kinerja pegawai Dinas Bina Marga Kota Banjarmasin. Metode yang digunakan dalampenelitian ini adalah evaluasi. Populasi dalam penelitian ini adalah Pegawai Dinas Bina Marga Kota Banjarmasin sebanyak 75 orang dan dianalisis secara kualitatif. Hasil penelitian menunjukkan: 1) perencanaan tata kerja dan koordinasi pada Dinas Bina Marga Kota Banjarmasin dalam meningkatkan Kinerja Pegawai meliputi kegiatan kedalam maupun keluar, terlihat belum menunjukkan hasil yang maximal, 2) solusi yang diberikan untuk meningkatkan kinerja seperti: a) kurangnya kuantitas sumber daya manusia sebagai pegawai yang diberi tugas secara administrative maupun teknis operasional menanggani pengembangan pembangunan fisikkota Banjarmasin, b) kurangnya kerja sama antar Dinas / Instansi yang berkompeten.Kata Kunci : Perencanaan, Koordinasi Dan Kinerja